Implementation of the Harmony Search Algorithm in Completing Lecture Scheduling - Abd. Rahman (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2018)
Scheduling lectures at a college is a routine activity every semester and is a process to implement events that contain components of courses and classes in time slots that contain components of time and space. The problem that often occurs in scheduling activities is the occurrence of conflicts between one schedule and another. One method to solve these problems is to use artificial intelligence (AI). One method in AI that is considered to provide a solution to scheduling problems is Harmony Search. Harmony Search is an area of computer science that bases its algorithms on music. The Harmony Search algorithm compares music with all its devices to optimization problems. For example, each musical instrument is associated with a decision variable; the musical pitch is associated with a variable value, harmony is associated with a solution vector. Like a musician who plays certain music, improvises playing a random tone, or based on experience to find a beautiful harmony, the variables in Harmony Search have random values or values obtained from iterations (memory) to find the optimal solution. By applying the Harmony Search algorithm to prepare the lecture schedule, it is hoped that an optimal arrangement of the lecture schedule can be created.